Investigation of phase formation in the system Fe2+/Co2+/O2/H2O - Frolova, Liliya; Derimova, Alona; Galivets, Iurii; Savchenko, Mariya; Khlopytskyi, Aleksey (Eastern-European Journal of Enterprise Technologies, 2016)
The dispersed iron oxide compounds are widely used as magnet carriers, pigments, catalysts, sorbents. Therefore, the study of phase formation in the system Fe2+/Co2+/O2/H2O, as well as the study of the influence of the basic oxidative environment parameters on the phase composition of iron (III) oxides over a wide pH range, and obtaining precipitates with a given chemical composition appear to be urgent. As a result of the studies involved, it was found that in the system Fe2+/Co2+/O2/H2O with constant cobalt content, the alkali consumption rate and the rate of product formation increase with increasing effective air flow rate. At constant rate of oxidation the oxidation time is reduced with the increase of cobalt content in the system. The phase composition of the resulting compounds is determined by the mode of OHCP (dynamic or static). Formation of СоxFe3-xO4 spinel structure occurs at pH 11–12 and air flow rate 4 min-1. In the presence of cobalt ions 3+, the rate of iron 2+compounds oxidation by atmospheric oxygen increases, because of their catalytic action.